2018
DOI: 10.21763/tjfmpc.452471
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Health Status and Yoga-Related Perceptions among Yoga Practitioner

Abstract: Aim: To determine self-perceived health status among yoga practitioners and their perceptions of yoga. Methods: This descriptive study was conducted in an online yoga platform during the month of December 2017. A total of 1602 individuals logged into the website during the data collection period, of which 158 volunteered to participate in the online survey. Data were collected using a questionnaire that included the participants' descriptive characteristics (6 questions) and their perceptions of yoga (5 questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In contrast, poor self-rated health and functional difficulties were negatively associated with yoga and mindfulness practice in this study. This finding supports earlier evidence that people with poor perceived health may not participate in yoga-related activities 44 . The finding also supports the evidence of reverse causality in which people who practice yoga may have better health outcomes including a better self-perceived health and functional ability 45 , 46 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, poor self-rated health and functional difficulties were negatively associated with yoga and mindfulness practice in this study. This finding supports earlier evidence that people with poor perceived health may not participate in yoga-related activities 44 . The finding also supports the evidence of reverse causality in which people who practice yoga may have better health outcomes including a better self-perceived health and functional ability 45 , 46 .…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, it was reported that individuals in Turkey preferred yoga for reasons such as sports (39.3%), spiritual development (24.0%), personal development (22.8%), and meditation (13.9%). 25 Also, healthy adults were determined to prefer yoga for reducing stress or T A B L E 1 The mean of the item and total scores from the pretest and posttest of the MAAS (N = 47)…”
Section: Discussionmentioning
confidence: 99%
“…Yoga is a very popular sport today; Yoga practice is a comprehensive health system that is beneficial for improving physical health and providing peace of mind and soul ((Moore & Pennington, 2021); (Cartwright et al, 2020)). Yoga in Sanskrit is "yuj," which means the union of breath, body, and soul ((Bhardwaj, 2019); (Erkin & Akçay, 2018); (Tiwari & Negi, 2019); (Hemamalini, 2018)). Yoga is a systematic condition for improving the body's condition, understanding the mind, and liberating the soul.…”
Section: Introductionmentioning
confidence: 99%